Influência do oídio no fruto de cajueiro anão - Maia, Lívia Karla Remígio (2014)
Recently, it has been observed the occurrence of typical symptoms of powdery mildew of the type described in Africa in all producing regions of Northeast Brazil. This study aimed to evaluate the effect of disease on biological and industrial quality of nuts and kernels cashew. Seeds collected for this study were derived from an experiment conducted in 2012, using the CCP-76 clone, whose aim was to evaluate different agricultural chemicals (defensives) to control powdery mildew cashew. This experiment consisted of five different defensives, and a control (no application) and three different application periods. The agricultural chemicals used were sulfur (Highcrop 680 SC 3ml/L), sulfur (Kumulus ® 3 g/L), triflumizole (Trifmine ® 0.5 g/L), tebuconazole (Tebuconazole ® 0.75 ml/l) and copper oxychloride (Recop ®, 3 g/L). Sprays were performed every 7, 14 and 21 days. From the collections of nuts this experiment was divided in four parts: germination, microbiological analysis, severity and quality of kernel. In the germination, were performed two tests, with and without phytosanitary treatment, the variables analyzed: density test, the percentage of germination and emergence, the length of the part aerial, root and seedling, stem diameter, number of leaves, leaf expansion, weight of shoot, root and seedling; were analyzed by 6 treatments and 6 randomized blocks. In the microbiological analysis were performed two assessments, in nut and kernel cashew, the variables analyzed: percentage of fungi of the genera Aspergillus, Eurotium, Cladosporium, Penicillium and Curvularia, in nut cashew followed by six treatments in six blocks and kernel cashew followed by six treatments in four blocks. In the severity were analyzed using a range of note: 0 - no injuries (0%), 1 - lesions covering up to 25% nut; 2 - lesions covering up to 50% nut, 3 - lesions covering up to 75% and nut and 4 - lesions reaching 100% nut, through a factorial 6x3 (five defensives and a control x three different application periods - 7,14 or 21 days). In the analysis of quality kernel cashew were analyzed the variables: weight total of kernel cashews (WTKC), weight mean of 10 kernels (WMK); calibration (CALIB): number of kernel/50g; opening cotyledon (COT OP): 0-No openings, 1 -small aperture, 2 - aperture average and 3 - very open; frequency (FREQ) = number of kernels with open cotyledons in a sample of 25 kernels analyzed; industrial income (II (%) = WTKC/5) ; entire healthy; brocade, stained, purple and spoiled (BMRE); broken (Brok): S - band, B - stopper and P – piece, by the same factor cited in the microbiological analysis. The seed germination is not correlated with seedling emergence. The Trifmine and Recop contribute to reduced seedling vigor. The sterilization process reduces seed germination and seedling development. The fungal genera Aspergillus and Penicillium are the most commonly associated with nuts and kernels cashew. The quality of the kernels cashew clone CCP-76 is not affected by the occurrence of powdery mildew when severity is equal to or below 2 on the scale 0 - 4.